The understanding of nurses who work in mental health regarding compulsory and involuntary hospitalization - Mariane da Silva Xavier; Marlene Gomes Terra; Maria Denise Schimith; Marinês Tambara Leite; Maria Henriqueta Luce Kruse; Cristiane Trivisiol Arnemann (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze the understanding of nurses working in the mental health services regarding compulsory and involuntary hospitalization referred to in the Brazilian Psychiatric Reform Law. Methodology: Qualitative research, with eight nurses from the mental health services. Data collection took place through an open interview, analyzed using Bardin's content analysis. Results: The nurses understand that when psychiatric hospitalization is recommended, the service user must be evaluated in the social and family context. They consider that both forms of hospitalization can cause distress and anxiety to the service user, due to this person finding herself in a place against her will. Conclusion: This study contributes to reflection regarding psychiatric hospitalization as a resource which must be used in specific situations. The success of community-based services is linked to a non-fragmented mental health service for effective implementation of the reorganization of psychiatric care.